Cloning and nucleotide sequence of Mycobacterium tuberculosis gyrA and gyrB genes and detection of quinolone resistance mutations. - Takiff, H E (1994)
The emergence of multidrug-resistant strains of Mycobacterium tuberculosis has resulted in increased interest in the fluoroquinolones (FQs) as antituberculosis agents. To investigate the frequency and mechanisms of FQ resistance in M. tuberculosis, we cloned and sequenced the wild-type gyrA and gyrB genes, which encode the A and B subunits of the DNA gyrase, respectively; DNA gyrase is the main target of the FQs. On the basis of the sequence information, we performed DNA amplification for sequencing and single-strand conformation polymorphism analysis to examine the presumed quinolone resistance regions of gyrA and gyrB from reference strains (n = 4) and clinical isolates (n = 55). Mutations in codons of gyrA analogous to those described in other FQ-resistant bacteria were identified in all isolates (n = 14) for which the ciprofloxacin MIC was > 2 micrograms/ml. In addition, we selected ciprofloxacin-resistant mutants of Mycobacterium bovis BCG and M. tuberculosis Erdman and H37ra. Spontaneously resistant mutants developed at a frequency of 1 in 10(7) to 10(8) at ciprofloxacin concentrations of 2 micrograms/ml, but no primary resistant colonies were selected at higher ciprofloxacin concentrations. Replating of those first-step mutants selected for mutants with high levels of resistance which harbored gyrA mutations similar to those found among clinical FQ-resistant isolates. The gyrA and gyrB sequence information will facilitate analysis of the mechanisms of resistance to drugs which target the gyrase and the implementation of rapid strategies for the estimation of FQ susceptibility in clinical M. tuberculosis isolates.